Primary and recombined emitting species in laser-induced plasmas of organic explosives in controlled atmospheres - Delgado-Pérez, Tomás; Vadillo-Pérez, José Miguel; Laserna-Vázquez, José Javier (Royal Society of Chemistry, 2014)
The main difficulties in spectral interpretation of laser-induced plasmas from species containing C, N, O or H rely on the crossroad concerning their origin: direct release from native bonds of the molecule or recombination of atoms and molecular fragments with ambient constituents. In order to add further insight into the issue, this paper presents the influence of the surrounding atmosphere (gas type and pressure) on the spectra of energetic nitro compounds (TNT and PETN). The study was completed with coincidental detection at high vacuum of both optical emission and mass spectra originated from the same laser event. We have proposed probable fragmentation pathways for the compounds taking into account the reactions that prevail over other routes depending on experimental conditions: laser fluence, pressure and the surrounding atmosphere. The suggested routes are supported by identification of many non-emitting, reactive species present in the plasma using the corresponding mass spectra.
Keywords: Plasmas producidos por láser; Laser induced breakdown spectroscopy; Laser ionization mass spectrometry; Ion photon detection; Energetic compounds; Molecular emission